Put yourself in their shoes: empathy leader / Dr. Sharfizie Mohd Sharip - Mohd Sharip, Sharfizie (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2021)
Empathy plays an important role in the development and maintenance of human relationships. Empathy is often confused with sympathy, where in fact there is a clear difference between the two. Sympathy focuses more on the feelings of love and affection whereas empathy entails a profound understanding of another person’s feelings. A person with empathy will put himself in the other person’s shoes and take an active interest in their predicaments. Why empathy matters?? In most organizations, the leader-employee relationship plays a crucial role in producing organizational effectiveness and productivity. A leader with a high degree of empathy will usually be able to understand behaviours in a relationship and use appropriate feelings and emotions in addressing the needs of the employees. Such leaders can form a meaningful bond with the employees and display a genuine concern for their well-being and emotions. Empathy is related to the leader’s interpersonal skills which enable him/her to respond appropriately and effectively to the employees’ behaviours Mahsud, Yukl, and Prussia, 2010). A leader with empathy usually expresses genuine humanity towards his/her subordinates (Mayfield, Mayfield, and Neck, 2017) such as giving compliments for a job well done (Mayfield, Mayfield, and Kopf, 1998). Such a demonstration of empathy and care can help the leader achieve the required behavioural enforcement among employees.